Life on mars from a Self-Determination Theory perspective: How astronauts' needs for autonomy, competence and relatedness go hand in hand with crew health and mission success - Results from HI-SEAS IV. (June 2019) - Goemaere, Sophie; Van Caelenberg, Thomas; Beyers, Wim; Binsted, Kim; Vansteenkiste, Maarten
Abstract: With the advent of long-duration interplanetary space missions, astronauts face new psychological challenges never observed before. Grounded in Self-Determination Theory, the objective of the present research was to study how astronauts' basic psychological needs relate to astronaut well-being and mission success, and how Mission Support could foster astronaut need satisfaction. Specifically, we examined how weekly ups and downs in astronauts' need for autonomy, competence and relatedness related to week-to-week fluctuations in a set of positive (i.e., self-endorsed motivation to follow operating procedures, cooperation with Mission Support members, happiness and performance) and negative outcomes (i.e., oppositional defiance towards operating procedures, irritation with Mission Support members and stress) during the Mars simulation HI-SEAS mission 4. Additionally, we examined whether variations in astronauts' needs could be predicted by variations in Mission Support's communication style in interacting with the crew. The study comprised six volunteers, three women and three men, between 25 and 36 years of age ( M  = 30, SD  = 4). The HI-SEAS IV mission simulated a yearlong stay on Mars. During the simulation, measures of autonomy, competence, relatedness with crewmembers and loved-ones at home, well-being, motivation, crew-ground interactions and performance were taken on a weekly basis. The data were analyzed using multilevel analyses. Overall, results indicated significant decreases in the experiences of autonomy as well as relatedness with both crewmembers and loved-ones at home, which aggravated as the mission progressed. Weekly experiences of all three need satisfactions, but in particular autonomy and relatedness with fellow crewmembers, were found to relate positively to weekly variations in self-endorsed motivation, cooperation, happiness and performance, and negatively to weekly variations in oppositional defiance, irritation, and stress. Moreover, week-to-week fluctuations in an autonomy-supportive communication style from Mission Support were found to relate positively, and a controlling style negatively, to weekly fluctuations in the crew's experience of autonomy, competence, and relatedness with crewmembers. Implications for future studies and human spaceflight are discussed. Highlights: Astronaut functioning is introduced from a Self-Determination Theory perspective. Weekly measures of the crew's needs and functioning were taken during HI-SEAS IV. Autonomy and relatedness with crewmembers in particular predicted crew functioning. Autonomy-support vs. control from the ground predicted the crew's need satisfaction. Implications for space agencies and future human space exploration are discussed.